Study on mechanics and permeability evolution of sandy mudstone during full stress-strain loading - Zhaoyun CHAI; Xiaoling WU; Xiangyu LIU; Xu LIU; Yuxu SHEN; Zipeng XIN (Meitan xuebao)
The evolution law of surrounding rock pore crack and its permeability change during soft rock roadway excavation is one of the basic scientific problems to be solved in water inrush disaster prevention and grouting reinforcement of weak surrounding rock. The hydraulic coupling tests of sandy mudstone with parallel and vertical bedding limited confining pressure are carried out by Rock Top multi-field coupling test system. The strength characteristics, failure forms and permeability of sandy mudstone under full stress-strain loading process are studied, and the evolution law of permeability in the process of sandy mudstone full stress-strain loading is clarified. The results show that the mechanical strength and permeability of sandy mudstone with bedding are anisotropic, the strength of parallel bedding rock samples in loading direction is higher than that of vertical bedding, but the permeability is opposite. The failure mode of parallel bedding rock samples in loading direction is mainly monoclinic shear and splitting failure, the circumferential strain of the crack is greater than the axial direction, manifested as body expansion. The full stress-strain curve can be divided into five stages: crack compaction, linear elasticity, stable crack growth, unstable crack propagation and post-peak residual strength. The permeability of rock samples in the first three stages remains constant, the permeability “jump” reaches the peak in the stage of unstable crack propagation, the peak of stress or post-peak residual strength, and the permeability change curve is in the shape of “N”. The failure mode of vertical bedding rock samples in the loading direction is mainly composed of axial tension splitting and circumferential shear slip, the axial strain of the crack is greater than the circumferential direction, manifested as axial compression. The full stress-strain curve can be divided into three stages: stable deformation, unstable deformation and post-peak residual strength. The permeability remains constant in the stable and unstable deformation stages, the permeability “jump” reaches the peak in the post-peak residual strength stage, and the permeability curve is in the shape of “∧”. The “sudden jump” of permeability is that the permeability induced by the connection of fracture network shows a sudden increase of geometric magnitude.